The Effect of E-Service Quality on User Loyalty with User Satisfaction as a Mediating Variable of LinkAja Users in Semarang City - Adiyanti, Regita Cahya; Firdaus, Firdaus (Economics and Business International Conference Proceeding, 2024)
This study aims to analyze and describe how much e-service quality affects user loyalty with user satisfaction as a mediating variable for LinkAja application users in Semarang City. This study uses a quantitative approach with a purposive sampling method using primary data obtained from distributing written instruments or questionnaires via google form with a Likert scale of 1-5. The natural population of this study were users of the Semarang city link aja. The sample used was 104 respondents who were users of the LinkAja application with the lemeshow formula. In this study, evaluate the hypothesis using SmartPLS analysis. Based on the SmartPLS analysis test that has been carried out, the results show that (1) E-Service Quality has a positive and significant effect on User Loyalty. (2) E-Service Quality has a positive and significant effect on User Satisfaction. (3) User Satisfaction has a positive and significant effect on User Loyalty. (4) User Satisfaction has a positive and significant effect on mediating the relationship between E-Service Quality and User Loyalty.